NDRG1 Activity in Fat Depots Is Associated With Type 2 Diabetes and Impaired Incretin Profile in Patients With Morbid Obesity - Stafeev, Iurii; Sklyanik, Igor; Mamontova, Elizaveta; Michurina, Svetlana; Shestakova, Ekaterina; Yah’yaev, Kamil; Yurasov, Anatoliy; Masnikov, Denis; Sineokaya, Maria; Ratner, Elizaveta; Vorotnikov, Alexander; Menshikov, Mikhail; et al. (Frontiers in Endocrinology, 2021)
Objective We aimed to investigate insulin-, mTOR- and SGK1-dependent signaling basal states in morbidly obese patients’ fat. We analyzed the correlation between the signaling activity, carbohydrate metabolism, and incretin profiles of patients. Methods The omental and subcutaneous fat was obtained in patients with obesity. The omental study included 16 patients with normal glucose tolerance (NGT) and 17 patients with type 2 diabetes mellitus (T2DM); the subcutaneous study included 9 NGT patients and 12 T2DM patients. Insulin resistance was evaluated using the hyperinsulinemic euglycemic clamp test and HOMA-IR index. The oral glucose tolerance test (OGTT) for NGT patients and mixed meal tolerance test (MMTT) for T2DM patients were performed. The levels of incretins (GLP-1, GIP, oxyntomodulin) and glucagon were measured during the tests. Signaling was analyzed by Western blotting in adipose tissue biopsies. Results We have shown equal levels of basal phosphorylation of insulin- and mTOR-dependent signaling in omental fat depot in NGT and T2DM obese patients. Nevertheless, pNDRG1-T346 was decreased in omental fat of T2DM patients. Correlation analysis has shown an inverse correlation of pNDRG1-T346 in omental fat and diabetic phenotype (HbA1c, impaired incretin profile (AUC GLP-1, glucagon)). Moreover, pNDRG1-T346 in subcutaneous fat correlated with impaired incretin levels among obese patients (inverse correlation with AUC glucagon and AUC GIP). Conclusions According to results of the present study, we hypothesize that phosphorylation of pNDRG1-T346 can be related to impairment in incretin hormone processing. pNDRG1-T346 in adipose tissue may serve as a marker of diabetes-associated impairments of the systemic incretin profile and insulin sensitivity.